Use of radioiodine in nuclear medicine—A brief overview. (12th November 2020) - Ferris, Trevor; Carroll, Laurence; Jenner, Sarah; Aboagye, Eric O.
Abstract : Radioiodines have a long history in nuclear medicine. Herein, we discuss the production, properties and applications of these versatile iodine‐based imaging and theragnostic agents. There are 38 isotopes of iodine (I) including one stable form ( 127 I). The most common radionuclides used in medical imaging and treatment, including Iodine‐123 ( 123 I), Iodine‐124 ( 124 I), Iodine‐125 ( 125 I) and Iodine‐131 ( 131 I), are discussed in this review. Abstract : Once produced by the methods reported in this review radioiodine can be administered to patients in a variety of forms and through different methods. Iodine isotopes are chosen based on their properties to either diagnose or treat diseases. We have found that there are numerous uses of radioiodine in nuclear medicine, with exciting uses emerging as part of current research.